2002
DOI: 10.1093/molehr/8.5.409
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelial cells in the pathogenesis of ovarian hyperstimulation syndrome

Abstract: Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication of treatment with fertility drugs. Using human lung microvascular endothelial cells (HUMEC-L) as an in-vitro model of OHSS, we have tested the hypothesis that the endothelium is a target of HCG in the pathogenesis of OHSS. Since OHSS is characterized by increased capillary permeability, we have investigated the production and action of vasoactive agents. When HUMEC-L were cultured with high doses of estradiol (E(2)), no significant changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…This stage of increased permeability may be required to distribute the high amounts of hormones needed to ensure the maintenance of the early pregnancy. Indeed, high doses of HCG significantly increased vascular permeability (Albert et al, 2002;Kitajima et al, 2006), and in rats, this was accompanied by a significant reduction of claudin 5 protein and mRNA expression (Kitajima et al, 2006). It may well be that the reduction of intercellular adhesion by HCG not only allows vascular expansion but also increases vascular permeability.…”
Section: Discussionmentioning
confidence: 97%
“…This stage of increased permeability may be required to distribute the high amounts of hormones needed to ensure the maintenance of the early pregnancy. Indeed, high doses of HCG significantly increased vascular permeability (Albert et al, 2002;Kitajima et al, 2006), and in rats, this was accompanied by a significant reduction of claudin 5 protein and mRNA expression (Kitajima et al, 2006). It may well be that the reduction of intercellular adhesion by HCG not only allows vascular expansion but also increases vascular permeability.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro studies with human lung microvascular endothelial cells have shown that the endothelium contains hCG receptors and responds to this gonadotrophin by releasing VEGF and increasing the amount of VEGFR-2 in the cell surface, suggesting that endothelial cells are involved in the pathogenesis of OHSS as VEGF producers (Albert et al, 2002). Figs 3 and 4 summarize the phases of VEGF expression and increased VP.…”
Section: Humansmentioning
confidence: 99%
“…OHSS is a self-limiting disorder with a broad spectrum of clinical manifestations related to increased capillary permeability and fluid retention brought about by many biochemical mediators, the most important being vascular endothelium growth factor (VEGF). 1 OHSS may be mild, moderate, or severe depending on the various clinical, radiological and laboratory parameters but the clinical impact of the syndrome depends on the variety of symptoms caused by the development of ascites, pleural effusion, hemoconcentration, reduced renal perfusion, and thrombotic complications. This iatrogenic entity can although affects 12e25% of IVF cycles, severe forms of ovarian hyperstimulation syndrome (OHSS) arises in 0.5e5% of assisted reproduction treatment (ART) cycles, and in its most severest form even known to cause maternal death.…”
Section: Introductionmentioning
confidence: 99%